Exploring undergraduate students' attitudes towards interprofessional learning, motivation-to-learn, and perceived impact of learning conflict resolution skills. Issue 2 (4th March 2018) - Vandergoot, Sonya; Sarris, Aspa; Kirby, Neil; Ward, Helena
ABSTRACT: Conflict resolution skills are important for all healthcare professionals as conflict and mis-communication can have detrimental effects on decision-making, potentially impacting significantly on patient care, morbidity, and mortality. Interprofessional learning (IPL) has been found to increase collaboration and improve collegial relationships and hence may be an appropriate way to increase conflict resolution skills among healthcare graduates. This study examined transference of conflict resolution skills, motivation-to-learn, and attitudes to IPL of medical ( n  = 52) and nursing ( n  = 74) undergraduate students who undertook an IPL conflict resolution program. Results indicated that motivation-to-learn, attitudes to IPL, and transfer of conflict resolution skills were significantly related to each other, even when controlling for other variables, such as age and gender. When comparing the two groups, undergraduate nursing students were found to have statistically higher motivation-to-learn and transference of conflict resolution skills, and reported a more positive attitude to IPL than medical students. Some of these differences may be attributed to lack of clinical placements for medical students in the first half of their degree at their university, giving them less opportunity to apply the conflict resolution skills taught, as well as less contextual relevance. This may potentially affect their motivation-to-learn and attitude to IPL thus impacting on how they perceive the relevance of learning conflict resolution skills. Without the contextual relevancy of placements at the time of learning for medical students, the newly acquired conflict resolution skills are less likely to transfer to practice in an optimal fashion.